Relationship of Preeclampsia History of Pregnant Women with the Incidence of Neonatal Asphyxia - Rezky Inayah Alfatihah; Rosdianah Rahim; Purnamaniswaty Yunus (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The neonate mortality rate (NMR) in Indonesia is still relatively high and has not met the predetermined target. One of the main causes of neonate mortality is neonatal asphyxia which can be caused by maternal factors, namely a history of preeclampsia in pregnant women. Objective: This study aims to determine the relationship between the history of preeclampsia in pregnant women and the incidence of neonatal asphyxia in RSUD Lanto Dg. Pasewang Jeneponto district for the period 2020-2021. Method: This study is a quantitative analytic study with a case control approach. the sample selection method is a purposive sampling technique of 364 samples consisting of 182 case samples and 182 control samples obtained from medical record data at Lanto Dg. Pasewang Jeneponto Regency for the period 2020-2021. The analysis technique used in bivariate analysis is the chi square test with a significance level of 5% (? = 0.05) with the help of statistical test software and the Odds Ratio (OR). Result: The results of the study based on the analysis obtained a p-value of 0.000 on the relationship between the history of preeclampsia of pregnant women with the incidence of neonatal asphyxia and the Odds Ratio (OR) value of 22.728. Conclusion: There is a relationship between the history of preeclampsia of pregnant women with the incidence of neonatal asphyxia at RSUD Lanto Dg. Pasewang Jeneponto Regency for the period 2020-2021 where a history of preeclampsia in pregnant women is 22.728 times more likely to cause neonatal asphyxia.